2023
DOI: 10.14740/jem884
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Calcific Pancreatitis and Its Association With Secondary Diabetes Mellitus

Gurusha Bahl,
Md Sadique Hussain,
Dinesh K. Upadhyay
et al.

Abstract: Chronic calcific pancreatitis (CCP) is an inflammatory illness that impacts the pancreas, causing calcifications and scarring inside the gland. Secondary diabetes, commonly referred to as type 3c diabetes mellitus (T3cDM), is one of the probable problems linked with CCP. T3cDM is a form of diabetes caused by an underlying illness or disorder of the endocrine systems. It is a rare cause of diabetes caused by pancreatic pathology. In the regions of Southeast Asian and India, it accounted for 15-20% of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that independent risk factors for cardiovascular events include neutrophil to platelet ratio (NPR) and neutrophil-lymphocyte ratio (NLR). Diabetes mellitus (DM) also significantly increases the risk of CVD through microvascular and macrovascular changes, as well as by augmenting other risk factors (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that independent risk factors for cardiovascular events include neutrophil to platelet ratio (NPR) and neutrophil-lymphocyte ratio (NLR). Diabetes mellitus (DM) also significantly increases the risk of CVD through microvascular and macrovascular changes, as well as by augmenting other risk factors (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%